Comparison of transoral and combined approach for surgical treatment of moderately advanced tongue and floor of the mouth cancer - A. V. Karpenko; R. R. Sibgatullin; A. A. Boyko; O. M. Nikolayeva (Опухоли головы и шеи)
Introduction. Surgical approach for oral cancer treatment is one of the key factors that determines oncologic effectiveness, risk of postoperative complications, need for reconstructive methods etc. Currently, there exists lack of strict criteria for using one or another approaches based on the sound scientific evidence for a primary tumor of given depth of invasion.Aim. The aim of the study is a retrospective comparative analysis of oncologic efficiency of transoral and combined approaches for surgical treatment of tongue and floor of the mouth moderately advanced carcinoma.Materials and methods. 75 patients aged between 30 and 80 years with tongue and floor of the mouth squamous cell carcinoma with depth of invasion from 10 to 20 mm were included into the study. In 29 cases the tumor was resected transorally (Group 1), in 45 – via combined approach (Group 2). Group 2 patients had more advanced tumors both locally and regionally. 13 patients of Group 1 and 27 patients of Group 2 underwent adjuvant radiotherapy. The following parameters were used for comparative analysis: the rate of local and regional recurrence, locoregional control, the rate of distant metastasis and Kaplan–Meyer overall survival.Results. Mean follow up was 33.77 ± 27.72 months (range 14–115 months). The rate of local and regional recurrence was higher in Group 2 (20 % vs 10.3 % and 22.2 % vs 17.2 % respectively). Locoregional control was better in Group 1 (72.4 % vs 62.2 %). The difference for neither of the above-mentioned parameters did not reach statistical significance. Median survival was statistically significantly better in Group 1: 66 ± 17.42 months vs 23 ± 3.85 months (p = 0.030). Poorer treatment results in Group 2 can be explained by a higher proportion of patients with more advanced tumors in this group.Conclusion. The results of the present study do not allow to conclude that combined approach has oncologic advantage over less aggressive transoral approach for tumors with depth of invasion from 10 to 20 mm. It is questionable to recommend the combined approach as a universal one for lesions with such a stage of local invasiveness.